2021
DOI: 10.3390/rs13061100
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Ecological Responses to Climatic Variability on Reclaimed and Unmined Lands Using Enhanced Vegetation Index

Abstract: Climatic impact on re-established ecosystems at reclaimed mined lands may have changed. However, little knowledge is available about the difference in vegetation–climate relationships between reclaimed and unmined lands. In this study, ecological responses to climatic variability on reclaimed and neighbouring unmined lands were estimated using remote-sensing data at the Pingshuo Mega coal mine, one of the largest coal mines with long-term reclamation history in China. Time-series MODIS enhanced vegetation inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Due to the particularity of the mining and reclamation layout, there are correlations among the indexes, and the legacy effects of mining should be quantified [ 53 ]. Consequently, the multiple regression equations cannot be established, and the degree of influence of different indexes is difficult to reflect.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the particularity of the mining and reclamation layout, there are correlations among the indexes, and the legacy effects of mining should be quantified [ 53 ]. Consequently, the multiple regression equations cannot be established, and the degree of influence of different indexes is difficult to reflect.…”
Section: Discussionmentioning
confidence: 99%
“…Vidal-Macua et al [35] and Li et al [9] reported that after mining, soil conditions became nutrient poor, leading to slower vegetation development and landscape fragmentation, and eventually reducing ecological stability. Moreover, with the increase in the reclamation time, establishing permanent vegetation cover may have restored landscape connectivity and previous ecosystem functions, and improved ecosystem productivity [54] and ecological stability [35]. Therefore, the NDVI for areas A and B were significantly positively correlated with ecological stability (p < 0.05).…”
Section: Explanation For Spatio-temporal Changes Of Ecological Stabilitymentioning
confidence: 99%
“…Relying only on traditional ground sampling experiments to monitor vegetation condition requires tremendous manpower and financial resources, which is not realistic. Compared with traditional methods, remote sensing monitoring can accomplish large-scale vegetation monitoring and provide effective and timely vegetation information [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%